Regulation of expression of the flagellin gene (hag) in Escherichia coli K-12: analysis of hag-lac gene fusions. - Komeda, Y (1979)
Previous studies have defined 28 genes necessary for the synthesis of the flagellar apparatus of Escherichia coli K-12. This study analyzed the influence of the flagellar genes on the expression of the hag gene (structural gene for flagellin). To this end, a hag::Mu d(Apr lac) mutant which had the lac genes fused to the promoter of the hag gene was constructed. This allowed the measurement of hag gene expression by detection of beta-galactosidase activity. The following observations were made. (i) The hag gene was expressed constitutively in Fla+ cells. (ii) hag gene expression was positively regulated by flaA, FLAB, flaC, flaD, flaE, flaG, flaH, flaI, flaK, flaL, flaM, flaN, flaO, flaP, flaQ, flaR, flaV, flaW, flaX, flaY, flaZ, flbA, and flbB genes.hag-lac expression was not observed in strains with these fla mutations. (iii) The hag gene was expressed in mutants with flaS, flaT, flaU, and flbC defects. Therefore, these genes were not involved in regulation of hag gene transcription.